Learning model of shot put sideways style for junior high school students - Ravinda Aris Munandar; Samsudin Samsudin; Sri Nuraini (UNIVERSITAS NEGERI JAKARTA POSTGRADUATE OF PHYSICAL EDUCATION DEPARTMENTS, 2022)
The purpose of this study is to develop a sideways style shot put learning model for junior high school students. This study uses a research and development model from Robert Maribe Branch, namely the ADDIE model (Analysis, design, development, implementation, and evaluation). The implementation phase is applied to class VII students at SMP Negeri 9 Pangkalpinang, class VII students at SMP Negeri 7 Pangkalpinang and class VII students at SMP Negeri 3 Pangkalpinang. So the total subjects in this study were 90 people. In this development research, the data used is data that uses instruments in the form of a questionnaire on the feasibility of developing a product and an instrument for the ability to shot put on the sideways style test. Paired Sample T-Test through the SPSS.26 application obtained the value of Sig. (2-tailed) of 0.000 < 0.05, it was concluded that there was an average difference between the pre-test and post-test on junior high school students. Then, the mean difference between pre-test and post-test is 14,833. This finding shows that the sideways style bullet put learning model program for junior high school students has a significant effect on increasing shot put ability